15 Motor Functional Neurological Disorder (MFND) in a large UK mental health service: clinical characteristics, medication prescription and response to outpatient cognitive behavioural therapy. (28th May 2019) - O'Connell, Nicola; Nicholson, Timothy; Wessely, Simon; David, Anthony S
Abstract : Objective: Studies on motor functional neurological disorder (mFND) often originate in neurology settings and are characterised by low sample sizes, and lack control groups. There are few prescription guidelines and no gold standard treatments. This study aims to establish mFND patients' socio-demographic and clinical characteristics, medication prescription patterns and patients' responses to outpatient cognitive behavioural therapy (CBT). Methods: This is a retrospective case-control study of mFND patients in contact with secondary mental health services in South London and Maudsley (SLaM) NHS Foundation Trust between 2006 and 2016. Data were obtained from anonymous electronic health records using the 'Clinical Records Interactive Search' (CRIS) database. Data were extracted on socio-demographic, clinical and medication variables. Control patients were a random sample of contemporaneous psychiatric patients treated within the same Trust and were matched at a ratio of 1:2. In a separate study, we employed these methods to identify mFND patients who attended an outpatient neuropsychiatry CBT clinic in SLaM, comparing therapeutic outcomes in mFND to patients with organic neuropsychiatric disorders (ONP) treated in the same clinic. Results: Our search returned 322 mFND and 644 control patients. Weakness was the most common functional symptom. mFND patients were more likely to be female, British, married, employed pre-morbidly, to have a carer and a physical health condition, but less likely to have had an inpatient psychiatric admission or to receive benefits. There was no difference in rates of childhood sexual and physical abuse between groups. A lower proportion of mFND patients received medication compared to controls (76.6% v. 83.4%, p<0.05), but of medication recipients, mFND patients were prescribed a higher number and variety of agents. We identified 98 mFND and 76 ONP patients attending the outpatient CBT service. Both groups showed significant improvements in psychological functioning post-CBT (measured with the CORE-OM, HoNOS-ABI, and PHQ-9), with physical symptoms improving in 49.4% of mFND patients. A logistic regression found acceptance of psychological formulations prior to CBT (p<0.02) was associated with improvement in physical functioning in mFND patients. Conclusions: mFND patients have a distinct socio-demographic profile and are prescribed a heterogeneous array of psychotropic and somatic medications. mFND patients treated in a specialist CBT clinic show similar improvements in psychological functioning to patients with organic neuropsychiatric disorders. This study establishes the socio-demographic profile of this under-studied patient group and could help guide the development of future therapeutic interventions and inform the design of a pilot RCT.